KARAKTERISTIK KIMIA KEFIR SUSU SAPI YANG DIFORTOFIKASI KOPI BUBUK ARABIKA SELAMA FERMENTASI - PUTRA G. A. A.; S. A. LINDAWATI; I N. S. MIWADA (Majalah Ilmiah Peternakan, 2022)
The purpose of this study is to fine out the chemical characteristics of kefir cow’s milk fortified arabica ground coffee. The research was conducted in July to September 2020 at the Laboratory of Animal Product Technology and Microbiology, Faculty of Animal Husbandry, Udayana University. The study used a completely randomized design (CRD) with five treatments and three replications. The five treatments were: fermented cow’s milk kefir without fortification of Arabica ground coffee (P0), fermented cow’s milk kefir with 1% fortification of Arabica coffee (P1), fermented cow’s milk kefir with 2% fortified Arabica coffee (P2), cow’s milk kefir fermented with fortified Arabica coffee powder 3% (P3), cow’s milk kefir was fermented with fortified Arabica coffee powder 4% (P4). The observed variables were lactose content, fat content, protein content and pH value. The results showed that the chemical characteristics of cow’s milk kefir fortified with Arabica coffee during fermentation had a significant effect (P<0.05) on the fat content of pH but was not significantly different (P>0.05) on lactose and protein content was in all tre- atments. The conclusion of this study is that kefir fortified with 2%, 3%, and 4% Arabica ground coffee gave good results according to Codex standards.